Pressure-controllable nano-film conductivity testing device and method thereof

By designing a nanofilm conductivity test device with controllable pressure, the problem that the prior art cannot test the ion conductivity of the proton exchange membrane under different pressure conditions is solved, and a more accurate evaluation of the performance of the electrolyte membrane is achieved. Repeatability.

CN119291307APending Publication Date: 2025-01-10NANJING UNIV OF SCI & TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411334491.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art cannot test the vertical ion conductivity of the proton exchange membrane under different pressure conditions, and cannot simulate hot pressing conditions, affecting the performance prediction of the battery in actual applications.

Method used

A nanofilm conductivity test device with controllable pressure was designed. By setting an annular positioning groove, piezoelectric sensor and spring buffering system on the carrier table, the pressure adjustment and real-time recording of the film samples were realized, combined with a constant temperature and humidity box. and electrochemical workstations, measure and calculate the vertical conductivity of the proton exchange membrane.

Benefits of technology

The nanofilm conductivity test is achieved under different pressure conditions, reducing sample damage, improving the repeatability and cost-effectiveness of the experiment, and being able to more accurately evaluate the electrochemical performance of the electrolyte film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119291307A_ABST
    Figure CN119291307A_ABST
Patent Text Reader

Abstract

The invention discloses a pressure-controllable nano-film conductivity testing device and a pressure-controllable nano-film conductivity testing method. The device comprises a shell, a current collector, an upper cover, a pressure regulator, a spring, a force application rod, a sample bearing table, a current collector, an insulating layer and a piezoelectric sensor. Wherein the pressure regulator is connected with the force application rod through the spring, and the spring is compressed to drive the pressure rod to downwards generate pressure on the film sample along the downward direction of the pressure regulator along the thread direction. According to the invention, the applied pressure is a continuous arbitrary value within the bearing range of the piezoelectric sensor, the pressure value is detected in real time, the damage of pressure mutation to the sample is effectively reduced through spring buffering, and the accuracy and constancy of vertical pressure application are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of secondary batteries and small scientific experimental devices, and in particular to a pressure-controllable nano film conductivity testing device and a method thereof. Background Art

[0002] A fuel cell reactor device is a device that converts chemical energy into electrical energy. It is composed of several groups of bipolar plate assemblies and several groups of membrane electrode assemblies stacked in sequence. The reducing agent and the oxidizing agent enter the fuel cell reactor device to complete the oxidation and reduction reactions and output electrical energy to the outside.

[0003] Membrane electrode (MEA) is mainly composed of a proton exchange membrane, a catalyst layer and a gas diffusion layer. During the production process of the membrane electrode, the membrane electrode needs to be hot pressed to ensure the bonding stability of the gas diffusion layer and the frame and to ensure the reliability of the membrane electrode.

[0004] The surface of the catalyst particles is covered with a thin layer of ion-conducting polymer, that is, the three-phase interface is wrapped by a thin layer of ion-conducting polymer. The oxidation reaction occurs at the three-phase interface of the ion exchange membrane, the catalyst and the oxidant, and the reduction reaction occurs at the three-phase interface of the ion exchange membrane, the catalyst and the reductant.

[0005] Thin-film secondary batteries are secondary batteries that use thin-film materials as positive and negative electrodes. They are composed of components such as positive electrodes, negative electrodes and electrolytes. When assembling thin-film secondary batteries, the anode, solid electrolyte film and cathode are stacked together in sequence to form a "positive-electrolyte-negative" structure, and the assembled battery structure is packaged.

[0006] For thin films, due to external pressure, the atoms or molecules inside the film will interact with each other, resulting in an isotropic stress field inside the film. The stress on the film can be divided into two aspects: normal stress and shear stress. Normal stress is the stress perpendicular to the film surface, and shear stress is the stress parallel to the film surface. The magnitude and direction of these stresses depend on the external loading conditions and the properties of the film material.

[0007] In engineering practice, the stress state of the membrane is usually calculated and analyzed according to specific circumstances to ensure that the membrane works safely and reliably within the design requirements.

[0008] Proton conductivity (σ) is a key parameter of the membrane. High proton conductivity can provide a high output voltage and current for the battery. The measurement of proton conductivity is generally divided into two ways: horizontal (in-plane) and vertical (out-of-plane).

[0009] Patent publication number CN 110988480A discloses a device and method for measuring the conductivity of a proton exchange membrane in the thickness direction. The device can control the contact between the membrane and both ends by adjusting weights, but the device cannot control or measure the pressure applied to the membrane.

[0010] Patent publication number CN 114295896 A discloses a method and device for testing anisotropic conductivity of proton exchange membranes. The device can test the conductivity of the proton exchange membrane in the plane and in the thickness direction under different temperature and humidity environments, but the device cannot test the ion conductivity in the vertical direction of the proton exchange membrane under different pressure conditions.

[0011] Therefore, the prior art urgently needs to simulate the hot pressing method such as Figure 8 The various working conditions encountered, such as temperature and pressure, are studied by exploring the conductivity of the film under different pressures to determine the maximum pressure that the film can bear. In this way, the device can not only evaluate the basic electrochemical properties of the electrolyte film under ideal experimental conditions, but also conduct tests under conditions close to actual application, thereby more accurately predicting the actual performance of the film in fuel cells and other devices, filling the gap between the experimental system and the industrial system. Summary of the invention

[0012] The present invention aims at the deficiencies of the prior art, and aims to provide a pressure-controllable nano film conductivity testing device and method thereof, so as to solve the problem in the prior art that the conductivity of the film under pressurized state cannot be tested.

[0013] To achieve the above-mentioned purpose, the present invention provides a pressure-controllable nano-film conductivity testing device;

[0014] The device includes:

[0015] Loading platform;

[0016] The upper surface of the carrier table is provided with an annular positioning groove for placing the thin film sample substrate;

[0017] The side of the supporting platform is connected to the current collector below;

[0018] An insulating layer and a piezoelectric sensor are stacked in sequence under the bearing platform;

[0019] The bearing platform and its lower parts can be placed or not placed in the frame formed by the upper cover and the outer shell;

[0020] The load-bearing platform is provided with a force-applying part:

[0021] The upper current collector, the pressure regulator and the force application rod are stacked in sequence;

[0022] The spring is nested in the internal rod of the pressure regulator, and slowly pressurizes the force rod with the upper knob of the pressure regulator. The spring buffers the pressure of the knob on the force rod to prevent the sudden increase of pressure from damaging the sample surface.

[0023] There is a cylinder at the end of the force-applying rod, and when the force-applying rod is pressed down, the cylinder contacts the film sample.

[0024] The assembly steps of the pressure-controlled nanofilm conductivity test device are as follows:

[0025] Step 1, selecting a proton exchange membrane sample that meets the standards;

[0026] Step 2, laying the proton exchange membrane substrate to be tested flat on the sample holding table so that it is completely embedded in the annular positioning groove;

[0027] Step 3: After fastening the upper cover, slowly rotate the pressure regulator to make the force rod pre-contact the surface;

[0028] Step 4: Rotate the pressure regulator gradually downward along the thread to compress the spring and control the force rod to gradually increase the pressure.

[0029] Until the target pressure value is reached;

[0030] Step 5: After reaching the set pressure target value, keep the pressure stable;

[0031] Step 6, placing the test device with the proton exchange membrane installed in a constant temperature and humidity chamber;

[0032] Step 7, connect the electrode of the electrochemical workstation to the current collector of the device; start the AC impedance test program, obtain the electrochemical impedance spectrum according to the measurement, calculate the proton exchange membrane resistance and calculate the proton exchange membrane vertical resistance according to the following formula:

[0033] Directional conductivity

[0034]

[0035] Where: R f :Film internal resistance

[0036] A: sample contact area, A = π × r 2 =0.1256cm 2

[0037] t: film thickness;

[0038] After that, the device is unloaded and the force rod is gradually separated from the sample after the spring is stretched. The sample is removed and the device is disassembled and cleaned. During the entire loading-unloading process, the pressure numerical control system records the pressure value in real time.

[0039] The present invention also provides an application of a pressure-controllable nanofilm conductivity testing device, the steps of which are as follows:

[0040] The support platform and the part below it are chosen not to be placed in the frame formed by the upper cover and the outer shell, that is, the outer shell of the device is removed, so that the device is used as an open device to control the temperature and humidity, and can measure the conductivity of temperature-sensitive materials under pressurized conditions.

[0041] The pressure-controllable nanofilm conductivity testing device of the present invention has the following beneficial effects:

[0042] 1. The present invention adds a spring buffer between the pressure regulator and the force-applying rod, which can reduce the damage to the sample caused by sudden pressure changes.

[0043] 2. The piezoelectric sensor of the present invention is connected to a data recorder via a data line, and can collect and display the pressure value borne by the sample in real time.

[0044] 3. Since an insulating layer and a sample carrier are placed above the piezoelectric sensor, this will also generate a certain amount of pressure on the piezoelectric sensor. Therefore, the present invention uses a numerical control system code setting to remove the pressure generated by the sample carrier and the insulating layer, so that the pressure display system pressure reading is 0 when the device is unloaded.

[0045] 4. The pressure-controllable nanofilm conductivity testing device of the present invention can be reused multiple times through steps such as disassembly and cleaning after the test, which can not only reduce costs but also enhance the repeatability of the experiment.

[0046] 5. The components of the equipment of the present invention are processed in a modular manner, and the processing dimensions can be adjusted according to actual conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below.

[0048] Figure 1 : A cross-sectional view of the overall device of the present invention.

[0049] Figure 2 : Overall device diagram of the present invention.

[0050] Figure 3 : Top view of the sample holding platform.

[0051] Figure 4 : Sample cover bottom structure diagram.

[0052] Figure 5 : Pressure knob structure diagram.

[0053] Figure 6 : Example 1 Test electrochemical impedance diagram.

[0054] Figure 7 : Example 2 Test ion conductivity.

[0055] Figure 8: Schematic diagram of the hot pressing method for preparing MEA.

[0056] Fig. 9 : Schematic diagram of spring parameters.

[0057] 1. Piezoelectric sensor

[0058] 2. Insulation layer

[0059] 3. Loading platform

[0060] 4. Bottom current collector (lower)

[0061] 5. Shell

[0062] 6. Upper cover

[0063] 7. Force rod

[0064] 8. Spring

[0065] 9. Pressure regulator

[0066] 10. Bottom current collector (top)

[0067] 11. Pressure display system

[0068] 12. Annular positioning groove

[0069] 13. Fixing screws DETAILED DESCRIPTION

[0070] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand the advantages and effects of the present invention from the contents described in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details of this specification can also be modified and changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0071] A pressure-controllable nanofilm conductivity testing device;

[0072] The device includes:

[0073] Carrying platform 3;

[0074] The upper surface of the carrier platform 3 is provided with an annular positioning groove 12 for placing the thin film sample substrate;

[0075] The side of the support platform 3 is connected to the current collector 4 below;

[0076] The insulating layer 2 and the piezoelectric sensor 1 are stacked in sequence under the supporting platform 3;

[0077] The support platform 3 and the parts below it can be placed or not placed in the frame formed by the upper cover 6 and the outer shell 5;

[0078] The bearing platform 3 is provided with a force applying part:

[0079] The upper current collector 10, the pressure regulator 9, and the force-applying rod 7 are stacked in sequence;

[0080] The spring 8 is nested in the inner rod of the pressure regulator 9, and slowly pressurizes the force-applying rod 7 with the upper knob of the pressure regulator. The spring 8 buffers the pressure of the knob on the force-applying rod 7 to prevent the sudden increase of pressure from damaging the sample surface.

[0081] There is a cylinder at the end of the force-applying rod 7, and when the force-applying rod 7 is pressed down, the cylinder contacts the film;

[0082] An annular positioning groove 12 with a diameter of 1.5 cm is provided on the upper surface of the supporting platform 3 .

[0083] The support platform 3 is fixedly connected to the insulating layer 2 and the piezoelectric sensor 1 by two screws 13 .

[0084] The insulating layer 2 is made of polyetheretherketone, which isolates the support platform 3 and the piezoelectric sensor 1, thereby reducing the influence of the piezoelectric sensor 1 on the proton conductivity test.

[0085] The upper cover 6 is also engaged with the outer shell 5 via an internal thread.

[0086] When the frame formed by the upper cover 6 and the outer shell 5 is set, one end of the lower current collector 10 is connected to the support platform 3, and the other end extends to the outside of the device through the opening of the outer shell 5. The piezoelectric sensor 1 (digital display) is used as the base of the device and is engaged with the outer shell 5 through a thread. The piezoelectric sensor 1 is connected to the pressure display system 11, and the pressure display system 11 displays the pressure value in real time.

[0087] The upper cover 6 is provided with a through hole which passes through the upper cover 6 from top to bottom and is centered at the geometric center of the upper cover 6 itself.

[0088] The pressure regulator 9 and the force-applying rod 7 are sequentially stacked in the through hole at the center of the upper cover 6 and fixed to the upper cover 6 by three screws.

[0089] The diameter of the cylinder is 4 mm, and when the force-applying rod 7 is pressed downward, the cylinder contacts the film sample.

[0090] The assembly steps of the pressure-controlled nanofilm conductivity test device are as follows:

[0091] Step 1, selecting a proton exchange membrane sample that meets the standards;

[0092] Step 2, laying the proton exchange membrane substrate to be tested flat on the sample holding table so that it is completely embedded in the annular positioning groove 12;

[0093] Step 3, after fastening the upper cover 6, slowly rotate the pressure regulator 9 to make the force-applying rod 7 pre-contact with the surface;

[0094] Step 4, gradually rotate the pressure regulator 9 downward along the thread, compress the spring 8, and control the force rod 7 to gradually increase the pressure until the target pressure value is reached;

[0095] Step 5: After reaching the set pressure target value, keep the pressure stable;

[0096] Step 6, placing the test device with the proton exchange membrane installed in a constant temperature and humidity chamber;

[0097] Step 7, connect the electrode of the electrochemical workstation to the current collector of the device; start the AC impedance test program, obtain the electrochemical impedance spectrum according to the measurement, calculate the resistance of the proton exchange membrane and calculate the vertical conductivity σ of the proton exchange membrane according to the following formula:

[0098]

[0099] Where: R f :Film internal resistance

[0100] A: sample contact area, A = π × r 2 =0.1256cm 2

[0101] d: film thickness;

[0102] After that, the unloading is performed, and after the spring 8 is stretched, the force-applying rod 7 is gradually separated from the sample; the sample is removed, and the device is disassembled and cleaned: During the entire loading-unloading process, the pressure numerical control system records the pressure value in real time;

[0103] Step 4 specifically includes selecting an applicable pressure range according to the parameter specifications of the spring 8, such as Fig. 9 , the calculation formula is as follows

[0104] k=G×d 4 ×n×D 3

[0105] G: The elastic modulus of the spring material, which indicates how well the spring material resists stretching or compression

[0106] d: diameter of the steel wire used in the spring

[0107] n: The number of effective coils in the spring that bear the load

[0108] D: average diameter of all coils of the spring

[0109] k: spring constant

[0110] P=k×δ

[0111] P: Spring load

[0112] k: spring constant

[0113] δ: Spring deflection.

[0114] Example 1

[0115] Referring to the drawings of the specification, a pressure-controllable nano film conductivity testing device provided by the present invention comprises a piezoelectric sensor 1, an insulating layer 22 is provided on the piezoelectric sensor 1, a sample carrier 3 is provided on the insulating layer 22, and a film substrate is laid on the sample carrier 3. An annular positioning groove 12 is provided at the center of the sample carrier 3, which has accurate positioning and reliable connection, and can play a role in fixing the film to be tested.

[0116] The annular positioning groove 12 on the sample supporting platform 3 is a cylinder with a diameter of 1.5 cm. The supporting platform 3 is connected to the lower current collector 4, and the other end of the lower current collector 4 is connected to the electrochemical workstation.

[0117] The force rod 7 moves perpendicularly to the sample carrier 3 under the constraint of the spring 8 to apply pressure to the film. When the spring is relaxed, the force rod 7 is 27 mm high from the surface of the sample carrier 3 at the highest point. As the spring 8 is gradually compressed, the force rod 7 is clamped with the proton exchange membrane and the sample carrier 3 to form an electrochemical system.

[0118] By rotating the pressure regulator 9, the force rod 7 is pre-contacted with the surface, and then the pressure regulator 9 is gradually rotated downward along the thread to compress the spring 8 and control the force rod 7 to gradually increase the pressure until the target pressure value is reached.

[0119] The housing 5, the upper cover 6 and the insulating layer 2 are all made of polyetheretherketone non-conductive material.

[0120] The measurement method specifically includes the following steps:

[0121] 1. Select proton exchange membrane samples that meet the standards;

[0122] 2. Lay the proton exchange membrane substrate to be tested flat on the sample carrier 3 so that it is completely embedded in the annular positioning groove 12;

[0123] 3. After fastening the upper cover 6, slowly rotate the pressure regulator 9 to make the force rod 7 pre-contact with the surface;

[0124] 4. Rotate the pressure regulator 9 gradually downward along the thread, compress the spring 8, and control the force rod 7 to gradually increase the pressure until the target pressure value is reached; after reaching the set pressure target value, keep the pressure stable;

[0125] 5. Connect the electrodes of the electrochemical workstation to the current collectors 4 and 10 of the device; start the AC impedance test program, measure and read the impedance value and calculate the conductivity;

[0126] 6. After unloading, the spring 8 is stretched and the force-applying rod 7 is gradually separated from the sample. The sample is removed and the device is disassembled and cleaned. During the entire loading-unloading process, the pressure numerical control system records the pressure value in real time.

[0127] In step 1: select the thin film substrate to be tested, the sample sheet should be smaller than the annular positioning groove 12 on the carrier 3, and the length and width of the sample sheet should be smaller than the length and width of the annular positioning groove 12, respectively, to ensure that the proton exchange membrane will not be damaged by the edge of the force-applying rod 7. Check the surface integrity of the membrane to be tested, visually observe under natural light or fluorescent light or observe under a microscope with the help of a magnifying device. If obvious defects (stains, scratches, incomplete film formation) are found in the appearance, discard it and take a new sample to be tested.

[0128] In step 3: the force rod 7 is polished with 0.05 μm α-Al 2 O 3 Polishing is performed, and ultrasonic treatment is performed in acetone and water for 10-100 minutes in turn to ensure the contact state between the force-applying rod 7 and the film to be tested.

[0129] In step 5: the proton exchange membrane applied between the lower current collector 4 and the upper current collector 10 is measured by an electrochemical workstation in the frequency range of 0.01 Hz-7 MHz, and the perturbation potential amplitude is 100 mV. When testing the vertical conductivity of the proton exchange membrane, an electrochemical impedance tester is used to apply an AC voltage to both ends of the upper current collector 10 and the lower current collector 4, and the R f Substitute the resistance value into the following formula to calculate the ionic conductivity σ of 30nm Nafion film at different pressures at 25℃ and 90%RH (see Appendix Figure 6 )

[0130]

[0131] in:

[0132] R f :Film internal resistance

[0133] A: Electrode area

[0134] t: film thickness.

[0135] Example 2

[0136] As an alternative, when the device housing 5 is removed and the device is used as an open device, the conductivity of the film under pressure under variable temperature and humidity conditions is tested.

[0137] Test preparation: Check the surface flatness of the electrode end of the force rod 7 and the sample carrier 3 to ensure that the surface is smooth without protrusions or depressions; check the surface integrity of the film to be tested;

[0138] Lay the proton exchange membrane substrate to be tested flat on the sample carrier 3 so that it is completely embedded in the annular positioning groove 12; after buckling the upper cover 6, slowly rotate the pressure regulator 9 to make the force rod 7 pre-contact with the surface; gradually rotate the pressure regulator 9 downward along the thread to compress the spring 8 and control the force rod 7 to gradually increase the pressure until the target pressure value is reached; after reaching the set pressure target value, keep the pressure unchanged;

[0139] Place the installed proton exchange membrane test device in a constant temperature and humidity chamber, set the constant temperature and humidity chamber parameters to: temperature 30°C, relative humidity 20-90% RH temperature and humidity environment, and let it stand for 2 hours to allow the proton exchange membrane to fully absorb water and swell. Start the AC impedance test program to measure, and after the test is completed, export the measurement data in the electrochemical workstation and enter The data processing software makes a vertical resistance temperature and humidity characteristic curve such as Figure 7 shown.

Claims

1. A pressure-controllable nanofilm conductivity testing device, characterized in that: The device includes: Loading platform; The upper surface of the carrier table is provided with an annular positioning groove for placing the thin film sample substrate; The side of the supporting platform is connected to the current collector below; An insulating layer and a piezoelectric sensor are stacked in sequence under the bearing platform; The bearing platform and its lower parts can be placed or not placed in the frame formed by the upper cover and the outer shell; The bearing platform is provided with a force-applying part. The force-applying part is composed of an upper current collector, a pressure regulator, and a force-applying rod stacked in sequence; The spring is nested in the internal rod of the pressure regulator, and slowly applies pressure to the force-applying rod as the upper adjustment knob of the piezoelectric sensor is turned; There is a cylinder at the end of the force-applying rod, and when the force-applying rod is pressed down, the cylinder contacts the film sample.

2. The pressure-controllable nanofilm conductivity testing device according to claim 1, characterized in that: A 1.5 cm diameter annular positioning groove is provided on the upper surface of the bearing platform.

3. The pressure-controllable nanofilm conductivity testing device according to claim 1, characterized in that: The supporting platform is fixedly connected to the insulating layer and the piezoelectric sensor by two screws.

4. The pressure-controllable nanofilm conductivity testing device according to claim 1, characterized in that: The insulating layer material is polyetheretherketone, which isolates the sample holding platform and the piezoelectric sensor.

5. The pressure-controllable nanofilm conductivity testing device according to claim 1, characterized in that: When the frame consisting of the upper cover and the outer shell is selected, one end of the lower current collector is connected to the sample support table, and the other end extends to the outside of the device through the opening of the outer shell; The upper cover is also engaged with the outer shell through internal threads; The piezoelectric sensor serves as the base of the device and is engaged with the housing through threads.

6. The pressure-controllable nanofilm conductivity testing device according to claim 5, characterized in that: The upper cover is provided with a through hole which is centered at the geometric center of the upper cover and passes through from top to bottom.

7. The pressure-controllable nanofilm conductivity testing device according to claim 6, characterized in that: The pressure regulator and the force applying rod are stacked in sequence in the through hole at the center of the upper cover and fixed to the upper cover by three screws.

8. The pressure-controllable nanofilm conductivity testing device according to claim 1, characterized in that: The cylinder has a diameter of 4 mm and when the force rod is pressed down, the cylinder contacts the film.

9. The method for assembling the pressure-controllable nano-film conductivity testing device according to any one of claims 1 to 9, characterized in that: The assembly method steps are as follows Step 1, selecting a proton exchange membrane sample that meets the standards; Step 2, laying the proton exchange membrane substrate to be tested flat on the sample holding table so that it is completely embedded in the groove; Step 3: After fastening the upper cover, slowly rotate the pressure regulator to make the force rod pre-contact the surface; Step 4: Rotate the pressure regulator gradually downward along the thread to compress the spring and control the force rod to gradually increase the pressure. Until the target pressure value is reached; Step 5: After reaching the set pressure target value, keep the pressure stable; Step 6, placing the test device with the proton exchange membrane installed in a constant temperature and humidity chamber; Step 7, connect the electrode of the electrochemical workstation to the current collector of the device; start the AC impedance test program, obtain the electrochemical impedance spectrum according to the measurement, calculate the resistance of the proton exchange membrane and calculate the vertical conductivity of the proton exchange membrane according to the following formula: Where: R f :Film internal resistance A: sample contact area, A = π × r 2 =0.1256cm 2 d: film thickness; After that, the unloading is carried out. After the spring is stretched, the force-applying rod is gradually separated from the sample. The sample is removed and the device is disassembled and cleaned. During the entire loading-unloading process, the pressure numerical control system records the pressure value in real time. Step 4 specifically includes selecting the applicable pressure range based on the spring parameter specifications. The calculation formula is as follows: k=G×d 4 ×n×D 3 G: The elastic modulus of the spring material, which indicates how well the spring material resists stretching or compression d: diameter of the steel wire used in the spring n: The number of effective coils in the spring that bear the load D: average diameter of all coils of the spring P=k×δ P: Spring load k: spring constant δ: Spring deflection.

10. Application of a pressure-controllable nanofilm conductivity testing device, characterized in that: The application is Removing the device casing allows the device to be used as an open device to facilitate temperature and humidity control and is used to measure the conductivity of temperature-sensitive materials under pressurized conditions.

Citation Information

Patent Citations

  • Device and method for measuring conductivity of proton exchange membrane in membrane thickness direction

    CN110988480A

  • Method and device for testing anisotropic conductivity of proton exchange membrane

    CN114295896A